Noise analysis of fully differential circuits - Spinelli, Enrique Mario (2012)
Fully-Differential (F-D) circuits are widely used because of its immunity to common mode interference and high dynamic range, being well suited for battery-powered devices. The analysis and design of this circuits call for specific techniques; this paper presents a method to estimate the output noise of F-D circuits due to its components. An example and also experimental data are included. © 2012 IEEE.